Ecological and economical problems in the oil and gas industry - Tula, N (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article the main aspects of ecological and environmental problems in the oil and gas industry are provided. There considered environmental problems arising from hydrocarbon production. The efficiency of oil and gas production from oil shale is considered. Recommendations for effective production of oil and gas with minimal impact on the environment and highest profit for economy are made